Informing care pathways and policies for children and youth with Indigenous perspectives to advance Canada's National Autism Strategy - Antony, Celina; Campbell, Madison; Côté, Stephanie; Bruno, Grant; Tinglin, Carolyn; Lai, Jonathan (Frontiers in Psychiatry, 2022)
In Canada, most services for Autistic people are provided by provincial and territorial governments. However, support for Indigenous Peoples (First Nations, Inuit, and Métis) are under federal responsibility and are outlined by a set of treaties and agreements with the Crown and a few regional governments. This patchwork results in barriers in service access and navigation challenges in many under-resourced communities, including under-diagnosis and potentially life-threatening outcomes. Designing equitable policy structures and processes would reduce harms and meaningfully interface with Indigenous and other racialized communities. The objective of this Policy Practice Review is to provide a framework for the discovery of appropriate care strategies addressing the conceptualization of autism in Indigenous Peoples and to understand the interactions between racialized Autistic peoples and the Criminal Justice System. First, we conducted environmental scans of publicly-accessible government services available in Canada pertaining to autism in Indigenous communities and the justice system, and explored the dissonance with beliefs and perceptions of autism in Northern Indigenous communities. Second, we focused on the interactions of Indigenous and other racialized populations, with an emphasis on Autistic children and youth with the justice system, an interaction that is often life-altering, downstream, and detrimental to health and wellbeing. The implications of this work include identifying the need for Indigenous-led knowledge and policy recommendations for Canada’s upcoming National Autism Strategy, informing the need for culturally appropriate multidisciplinary care and facilitating the coordination between health and social services for these communities.